SISTEM INFORMASI PENGELOLAAN BANK SAMPAH BERBASIS ANDROID DI WILAYAH KAB. TEGAL - Syefudin . (Indonesian Journal of Informatics and Research, 2021)
The Kaliwungu Sejahtera Waste Bank or commonly called BASAMKAS is one way of managing household-scale waste, which focuses on empowering the community in managing household waste. which has economic value. The transaction process carried out at the BASAMKAS waste bank is still less effective and efficient where customers come to the Garbage Bank location with garbage and savings books, then the officer records the results of customer deposits and details of waste savings using notes in the book. Then the clerk wrote back in the savings book belonging to the customer. This study aims to create an android-based waste bank management information system so that activities in the waste bank are in one system. The Android-based waste bank management system will make it easier for officers to make reports and make it easier for customers to transact. Customers or officers do not have to worry about their books being lost or damaged because all data is already stored in the database.